Present and future for confessional ideological companies - Perales Agustí, Montserrat (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
We can see a summary with the problems and defense of the Fundamental Rights of individuals who work for ideological companies and the problems European countries and other states, due to their separation churchstate and the defense of the principles of liberty, justice and equality, must face on a context of co-existence of their own legal systems and the laws of the religious communities. The exposition of the increasing trend of ideological confessional companies inclined to extend their activities and the defense of their norms and values, which differ sometimes from the principles of the European society. A summing up of the few existing laws covering this matter and the problems courts must face when deciding the importance of fighting against any form of discrimination, based on religion or belief, presented by individuals or religious communities. The necessity of passing similar laws for ideological companies and so avoid the confrontation of Fundamental Rights at courts and the necessity of protecting the aim of individuals and religious communities to maintain and save their principles and values.
Keywords: Ideological company; ideological confessional companies; labor relations and human resources; fundamental rights; freedom of religion; religious communities; labor discrimination.